Raising EU productivity through innovation - Reinhilde Veugelers; Frederic Warzynski (Bruegel, 2022)
Research and development is seen as a key contributor to growth because it generates knowledge, leading to new or improved products through product innovation, and makes firms more efficient at producing goods through process innovation. Firm- level studies generally find evidence of strong positive productivity effects for firms that invest in R&D. In this context, digital systems could be an important driver of productivity growth, particularly in combination with investments in R&D. But there has been little hard evidence of a significant productivity boost from digital technologies. How the relationship between productivity growth, innovation and digital technology adoption plays out is particularly important for the European Union, where productivity growth has long been weak. Researchers from the MICROPROD project (https://www. microprod.eu/) have assessed the effect of technology investment on productivity and performance. Combining recent unique firm-level data and state-of-the-art research methodologies, MICROPROD research provides a better overview of which firms are most likely to adopt digital technologies and to innovate, and to turn these investments into productivity growth.
Keywords: 330; innovation